2003
DOI: 10.1002/path.1442
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus infection in colorectal neoplasms associated with inflammatory bowel disease: detection of the virus in lymphomas but not in adenocarcinomas

Abstract: Epstein-Barr virus (EBV) is associated with several lymphoid and epithelial human malignancies. The latter include gastric adenocarcinomas, while sporadic colorectal adenocarcinomas (CRCs) have been reported to be EBV-negative. Recently, increased numbers of EBV-infected B lymphocytes have been detected in intestinal mucosal samples affected by ulcerative colitis (UC) and, to a lesser extent, Crohn's disease (CD). Both CRC and colorectal non-Hodgkin's lymphoma (NHL) are recognized complications of inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 29 publications
3
42
1
Order By: Relevance
“…The importance of infectious pathogens in CD is still debated, EBV is one of the most common pathogen which can be detected in colonic mucosa of CD patients. 29 Wong, et al, detected EBV in IBD associated lymphomas, but not in IBD associated CRC-s. 30 In addition, Dayharsh et al identified 18 IBD patients diagnosed with lymphoma at the Mayo Clinic, in Rochester, Minnesota, between 1985 and 2000. 31 Six patients diagnosed with lymphoma were on AZA or 6-MP.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of infectious pathogens in CD is still debated, EBV is one of the most common pathogen which can be detected in colonic mucosa of CD patients. 29 Wong, et al, detected EBV in IBD associated lymphomas, but not in IBD associated CRC-s. 30 In addition, Dayharsh et al identified 18 IBD patients diagnosed with lymphoma at the Mayo Clinic, in Rochester, Minnesota, between 1985 and 2000. 31 Six patients diagnosed with lymphoma were on AZA or 6-MP.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive therapy in IBD patients can reactivate latent EBV infections, which can lead to enteropathy (16). In particular, EBV-associated enteropathy frequently occurs during intensive immunosuppressive therapy in UC patients (16,17). In addition, enteropathy that is associated with the reactivation of latent EBV infections has also been reported to occur following both allogeneic stem cell transplantation and intestinal transplantation (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive therapy in IBD patients can reactivate latent EBV infections, which can lead to enteropathy (16). In particular, EBV-associated enteropathy frequently occurs during intensive immunosuppressive therapy in UC patients (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up studies failed to show any evidence that EBV was detected at a significantly higher rate in colorectal carcinoma (Grinstein et al, 2002;Yuen et al, 1994), even in higher risk populations such as patients with ulcerative colitis (N.A. Wong et al, 2003). In the case of Cytomegalovirus (CMV), early limited studies have detected CMV genome in the colon carcinoma tissue, whereas controls from normal colons and cases of Crohn disease were negative (Huang & Roche, 1978;Hashiro et al, 1979).…”
Section: Other Virusesmentioning
confidence: 99%